Concepções de Corpo segundo Pacientes e Profissionais de Medicina Tradicional Chinesa do Centro de Saúde Escola do Butantã - Cintra, Maria Elisa Rizzi [UNIFESP] (2010)
The present study searched to understand how health professionals and patients of the Teaching Health Center Samuel B. Pessoa/ Butantã (CSEB), in São Paulo, perceive the body in contact with Traditional Chinese Medicine (TCM) configured as a therapeutic of different medical rationality from Biomedicine. Thus, the initial hypothesis was that in the contact with acupuncture new forms of thinking the body, health and illness can be apprehended. The investigation was developed with an ethnographic approach in the clinic of acupuncture of the CSEB, from September 2008 to April 2009. The observations had revealed a heterogeneous group of professionals and patients (as to the age, gender, religion and territorial origin) in contact with the TCM. The majority of the interviews reveal that people´s contact with Traditional Chinese Medicine was given by personal experiences with distress, pain and suffering related to their bodies, having them appealed to the acupuncture as resource and, later, seeking its beddings. Diverse ways of thinking about ill / health and of using the body were identified, but always sustains by two opposites but complementary dimensions: health body and not health body. And tree forms of how to perceive the body also were identified: Ideas about the body, Reactions and Techniques of the Body. From the experience with TCM, people get in touched and embodied, partly, with a body conception that consider the energetic and invisible dimensions as formerly than the organic material. It also counts that, in this process, they had changed some daily habits and the way they perceived and used the body related with Meditation, Exercises and food provisions. Based in experiences and conceptions of body previous to the treatment, they had disclosed very distinct senses for the experience of each one. For example, the body was defined as ―a sanctuary‖, as ―a structure‖, ―the soul‘s car‖, among others.